Factors Associated With Hypertension among Adult Patients in Biratnagar - Basnet, Saraswati (Tribhuvan University Journal, 2019)
Hypertension: a major public health challenge worldwide and it is also considered as a major public health challenge, affects one billion persons worldwide. The aim of study was to identify risk factors of hypertension. Hospital based case-control research design was used for this study. The study was conducted at Koshi Zonal Hospital in Biratnagar. Non probability purposive sampling technique was used. The total sample size was 192. A semi- structure an interview schedule consisting semi-structured questionnaires were used to measure the risk factors of hypertension. The data was analyzed by using both descriptive and inferential statistics. The finding of this study revealed that more than forty four percent cases and controls was age 40-50 years. Fifty six percent of cases and controls were male. About forty three percent of cases and thirty three percent of controls were overweight. Forty three percent of cases and nine percent of controls were past smoker. Seventy three percent of cases were alcoholic whereas only thirty four percent of cases were non alcoholic. Hypertension was no significant association with obesity, family history, smoking, alcoholism and exercise. Above results concluded that it can be association with obesity, family history of hypertension, smoking, and alcohol consumption and doing light exercise.